Malus x 'Jewelberry' Jewelberry Crabapple: FPS-392/FP392, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides comprehensive information on growing crabapples, including their ideal growing conditions, such as sunny locations with good air circulation and well-drained soil. It details the various characteristics of crabapple trees, including size, flower and fruit color, growth habits, and disease resistance. The document is about the Jewelberry' crabapple and, also highlights different cultivars, such as ‘Prairifire’ and ‘Sugar Tyme’, their uses in landscaping, and their adaptability to urban environments. Additionally, it addresses common pests and diseases that affect crabapples and offers recommendations for selecting disease-resistant varieties. Original publication date October 1999.